MOTOR PERFORMANCE OF CHILDREN IN THE EXECUTION OF THE MOTOR TASK OF THE VERTICAL JUMP (Fiep Bulletin - online, 2015)
The vertical jump consists in a basic, complex and high impact physical capacity.  It is known that the exposition on the loads is essential in infancy, therefore is strong related to the long bones growth, however when practiced erroneously how much the loads and repetitions can generate problems. Thus, this study was fulfilled objectifying to evaluate the dynamic characteristics of the Ground Reaction Force (FRS) of 4 to 12 year-old children's vertical jump. Specifically:  a) compare the dynamic and space-timing variables between boys and girls; b) correlate such variables and c) analyze qualitatively the format of the vertical force curves. One selected for study the variables: propulsion and vertical landing peaks, propulsion and landing peaks in the horizontal direction, vertical propulsion gradient, flight time, vertical and of damping impulses. After the UDESC Ethics Committee approval had been selected, of systematic accidental form, 52 pertaining to school of the Florianópolis/SC public education net, being 30 girls (8±2,02 years) and 22 boys (9±1,93 years).  In the data collection was used an AMTI-OR6-5 force platform integrated to the Peak Motus system, with sampling frequency of 900Hz. After identification and adaptation, the children had executed three valid vertical jump. In the data processing was used the system Peak Motus and program SAD32.  In the data characterization, descriptive statistics was used; in the comparison between genders, Student test "t"; to verify the relation between variables, the Spearman Brown correlation. All the analyses with p0,05.  In the comparison between genders, performance in the jump execution for the boys was evidenced better. There were significant correlations in the majority of the variables in the three jump phases, indicating the interdependence between the variables. The high variability of the data points with respect to the individual children strategy in the execution of this motor task.
Keywords: Vertical jump; biomechanics; children.